ʿArafāt al-ʿāshiqīn wa-ʿaraṣāt al-ʿārifīn. Volume 7, Nūn-Yāʾ - Awḥadī, Taqī al-Dīn, (Miras Maktoob, ISBN: 9789004365452., 2019)
In Persian literature, tadhkira ('note', 'memorandum') works are for the most part collections of biographies of poets, combined with selections from their writings. The earliest such work is Dawlatshāh Samarqandī's Tadhkirat al-shuʿarāʾ (completed in 892/1487), which set a standard for posterity. The tadhkira genre was especially popular in the 10th/16th century and following. The present work by Taqī al-Dīn Awḥadī (alive in 1042/1632-33) is a good example of this. Born in Isfahan in 973/1565, as a young man his poetical talent was commended by, among others, the poet ʿUrfī Shīrāzī (d. 999/1591). After some time in the entourage of Shāh ʿAbbās I and a six-year stay in Iraq, he left Persia to try his luck at one of the courts in India. The present work, completed in 1024/1615, was written for a high official at the court of Jahāngīr. It contains about 3500 entries on Persian poets from the earliest times until his own day.